Ochrona polskich grobów i cmentarzy na terytorium Uzbekistanu w świetle dwustronnych regulacji traktatowych - Staszewski, Wojciech (PRAWO i WIĘŹ, 2025)
The protection of graves and cemeteries as places of burial is an essential element of the care of the national heritage and an expression of the formation of the national memory. Therefore, efforts to commemorate and protect the graves of Poles buried outside Poland are extremely important. Uzbekistan has numerous burial sites of Polish soldiers and civilians, as many military units of the emerging Polish army in the USSR were stationed there. This paper lists and analyses bilateral treaty provisions relating to cooperation in the protection of graves and cemeteries. It examines whether international agreements between Poland and Uzbekistan have provided a formal basis for such cooperation, and how this cooperation is carried out.